The Querist : Containing Several Queries Proposed to the Consideration of the Public - Berkeley, George, 1685-1753 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Querist" by George Berkeley is a philosophical treatise written in the early 18th century. This work is structured around a series of thought-provoking queries aimed at addressing the socio-economic situation of Ireland and the nature of wealth and industry. Berkeley articulates critical questions that explore whether idleness can coexist with wealth, the essence of poverty in a well-fed society, and the role of government in promoting industry among its citizens. At the start of "The Querist," Berkeley poses a multitude of queries that challenge conventional notions of wealth, labor, and societal prosperity. He questions the relationship between industry, poverty, and the distribution of resources, emphasizing the importance of sound governance in fostering a productive populace. Through these carefully constructed questions, he invites readers to reflect on the moral and practical implications of various customs and economic practices, such as luxury spending and the nature of money itself, effectively setting the stage for a philosophical exploration of economic theory and its application in 18th-century Ireland. (This is an automatically generated summary.)
Release date is 2003-10-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Great Britain -- Economic policy; Wealth; Great Britain -- Economic conditions -- 18th century